THE INFLUENCE OF SMART LADDER LEARNING Media ON THE UNDERSTANDING OF MATHEMATICAL CONCEPETS IN ADDITION AND SUBRACTION MATERIAL FOR GRADE I STUDENT - Safinatunnaja; Eka Fitri Puspa Sari; Imelda Ratih Ayu (Journal of Practice Learning and Educational Development, 2025)
This study aims to determine the effect of smart ladder learning media on the understanding of mathematical concepts in the addition and subtraction material of grade I elementary school students at SDN 10 Payaraman. The type of research used is quantitative research with only posttest group design. The subjects of the study consisted of 35 grade I students divided into two groups, Class IA (20 students) as the experimental class and class IB (15 students) as the control class. Data collection techniques include observation, test methods and documentation. The results of the study showed that students who learned using the smart ladder learning media obtained better learning outcomes as evidenced by the average posttest score of the experimental class of 85.5, while the control class obtained an average score of 51.33%. This difference shows that the use of smart ladder learning media has a positive impact on the understanding of mathematical concepts in the addition and subtraction material. Therefore, this media is an alternative support in the mathematics learning process in the early grades of elementary school.